DOP002 Vedolizumab treatment persistence up to 3 years: post hoc analysis in vedolizumab-naïve patients from the GEMINI LTS study. (16th January 2018) - Vermeire, S; Loftus Jr, E V; Khalid, J M; Tudor, D; Akbari, M; Demuth, D; Peyrin-Biroulet, L
Abstract: Background: Vedolizumab (VDZ) is a gut-selective humanised monoclonal antibody that binds to α4 β7 integrin, approved for the treatment of patients with moderate to severe ulcerative colitis (UC) and Crohn's disease (CD). The objective of this study was to evaluate long-term (3 years') treatment persistence of VDZ in a de novo cohort from the GEMINI long-term safety (LTS) study; a population without prior VDZ exposure and, thus, more likely to represent patients seen in clinical practice who have not participated in randomised controlled trials. Methods: A post hoc analysis of interim data from GEMINI LTS (cut-off date 21 May 2015) was performed in de novo patients who received VDZ every 4 weeks. VDZ treatment persistence was assessed using Kaplan–Meier survival analysis. Treatment discontinuations due to lack of efficacy and adverse events (AEs) were considered for the analysis. Patients discontinuing for other reasons (protocol violation, subject withdrawal, lost to follow-up) were right-censored. Treatment persistence was further stratified by prior tumour necrosis factor (TNF) antagonist therapy failure; a log-rank test assessed statistical difference between TNF subgroups. Results: Data for 421 patients (UC 190; CD 231) were analysed: 61% of patients with UC and 74% with CD had prior TNF antagonist failure. Median disease duration (range) was 5.8 years (0.4–50.2) for UC and 8.3 years (0.3–50.0) for CD. A total of 218 patients discontinued VDZ during follow-up; of these, 46% was due to lack of efficacy and 27% to AEs. The respective survival probabilities of continuing VDZ at 1 and 3 years were 77% and 64% in patients with UC, and 67% and 55% in patients with CD. These probabilities were higher in patients without vs. with prior TNF antagonist failure (Figure 1; UC p = 0.18: 81% vs. 75% [1 year], 69% vs. 61% [3 years]; CD p < 0.01: 84% vs. 60% [1 year], 68% vs. 51% [3 years]). The respective cumulative probabilities of treatment discontinuation due to lack of efficacy at 1 and 3 years were: 16% and 22% (UC), and 26% and 33% (CD); and due to AEs were 8% and 17% (UC), and 10% and 18% (CD). Conclusions: Nearly two-thirds of patients with UC and more than half with CD persisted with VDZ treatment for 3 years. Rates of VDZ discontinuation due to AEs were low and VDZ treatment persistence rates were higher in patients without prior TNF antagonist failure. These data support the long-term effectiveness and favourable safety profile of VDZ, and suggest improved outcomes of VDZ treatment in TNF antagonist-naïve patients.